Dry eye syndrome in thyroid-associated ophthalmopathy - A. F. Brovkina; O. N. Steshenko; O. D. Zhukova (Oftalʹmologiâ, 2015)
Purpose: The pathogenesis of keratoconjunctivitis sicca in patients with thyroid eye disease is presented. The influence of therapy by a HYLO-PARIN® on a condition of a tear film in patients with various forms of thyroid eye disease is assessed. Methods: 34 eyes (17 patients) with thyroid eye disease were investigated. Dry eye evaluations included Shirmer and Jhones testing, tear film break-up time, corneal fluorescein staining. Patients were treated with HYLOPARIN ® (Ursapharm, Germany).Results: Study showed that HYLO-PARIN® resulted in marked improvement as assessed by subjective complaints, Schirmer’s test, tear film break-up test.Conclusion: HYLO-PARIN® provided relief from the signsand symptoms of dry eye syndrome at patients with various forms of thyroid eye disease.